2020
DOI: 10.1039/d0fo00439a
|View full text |Cite
|
Sign up to set email alerts
|

The ameliorative effect of Lactobacillus plantarum Y44 oral administration on inflammation and lipid metabolism in obese mice fed with a high fat diet

Abstract: In our previous studies, Lactobacillus plantarum Y44 showed antioxidant activity and favorable gastric and intestinal transit tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 67 publications
3
35
0
1
Order By: Relevance
“…Probiotic mixture VSL#3 was found to reduce the levels of TNF-α and concomitantly augment IL-10 in a diabetic mice model fed for 12 weeks [26]. Similar studies have shown the effects of probiotic lactobacilli on inflammatory markers [20,27]. Our findings are consistent with previous reports suggesting the anti-inflammatory potential of Lact.…”
Section: Discussionsupporting
confidence: 91%
“…Probiotic mixture VSL#3 was found to reduce the levels of TNF-α and concomitantly augment IL-10 in a diabetic mice model fed for 12 weeks [26]. Similar studies have shown the effects of probiotic lactobacilli on inflammatory markers [20,27]. Our findings are consistent with previous reports suggesting the anti-inflammatory potential of Lact.…”
Section: Discussionsupporting
confidence: 91%
“…Consumption of oily foods continually produces triglycerides, and adipocytes start to die, thereby activating immune cells, causing inflammatory conditions such as fatty liver disease and inflammatory bowel disease [ 28 , 29 ]. Several studies have reported that consumption of lactobacilli is associated with decreased body fat [ 30 , 31 ]. Lactobacillus gasseri BNR17 (BNR17), isolated from human breast milk, inhibited increases in adipocyte tissue weight in high-sucrose diet-fed Sprague-Dawley rats [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus gasseri BNR17 (BNR17), isolated from human breast milk, inhibited increases in adipocyte tissue weight in high-sucrose diet-fed Sprague-Dawley rats [ 30 ]. Oral treatment with L. plantarum Y44 and a high-fat diet decreased the epididymal adipocyte area compared with that of the HFD group [ 31 ]. The present study demonstrated and confirmed that L. plantarum K2 and K6 have anti-obesity effects in rats like other lactobacilli.…”
Section: Discussionmentioning
confidence: 99%
“…P. freudenreichii MJ2 effectively inhibited lipid accumulation and adipocyte differentiation, and the antiobesity effect of P. freudenreichii MJ2 was proven to be superior to that of L. plantarum, which is known as an antiobesity probiotic bacterium. L. plantarum shows improvement effects on lipid metabolism disorder in HFD-fed mice by modulating gut microbiota 28 .…”
Section: Discussionmentioning
confidence: 99%